2011
DOI: 10.3949/ccjm.77a.10025
|View full text |Cite
|
Sign up to set email alerts
|

Can a bowel preparation exacerbate heart failure?

Abstract: Polyethylene glycol solutions, used for bowel preparation before colonoscopy, in theory pass through the colon without any absorption of water. However, several investigators have reported that these solutions do increase plasma volume. This review compares polyethylene and sodium phosphate bowel preparations and their effects on patients with heart failure, and also offers recommendations for patients with heart failure who need colonoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…However, many studies have demonstrated poor compliance because of the large volumes of these solutions [18]. The full-dose PEG regimen has been associated with complications such as Mallory-Weiss tears due to the vomiting [19], and a large amount of PEG expands plasma volume by 6-17%, which may exacerbate heart failure in some patients [20].…”
Section: Discussionmentioning
confidence: 99%
“…However, many studies have demonstrated poor compliance because of the large volumes of these solutions [18]. The full-dose PEG regimen has been associated with complications such as Mallory-Weiss tears due to the vomiting [19], and a large amount of PEG expands plasma volume by 6-17%, which may exacerbate heart failure in some patients [20].…”
Section: Discussionmentioning
confidence: 99%
“…Also, coronary heart disease has been identified as a risk factor for severe desaturation and relevant electrocardiographic changes during endoscopic sedation[ 130 ]. Furthermore, several studies have found that these solutions may be harmful to patients with heart disease due to the potential increase in plasma volume and their effects on electrolyte disturbances[ 131 ].…”
Section: Specific Clinical Settingsmentioning
confidence: 99%
“…However, some recent case reports have raised safety concerns related to the occurrence of cardiac events after the use of PEG-based bowel preparations. A few case reports involving patients who experienced heart failure exacerbation after using PEG-based bowel preparations for colonoscopy have been published [ 4 , 5 , 6 ]. Furthermore, another case report has suggested the possible association of PEG use with the risk of cardiac arrhythmia [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, these bowel preparation agents can cause adverse events, including electrolyte imbalances and acute renal failure [ 2 , 3 ]. Case reports of rare adverse cardiac events, such as heart failure exacerbation related to bowel preparation, have been published [ 4 , 5 , 6 ]. Recently, one case report suggested the possible association of purgative use and the development of atrial fibrillation (AF) [ 7 ].…”
Section: Introductionmentioning
confidence: 99%